Association Between Autoimmune Thyroiditis and Thyroid Cancer: A Systematic Review of Studies in the Indian Population - Borah, Monalisha Saikia; Sharma, Ajanta; Mazumder, Tahmina; Bhuyan, Amrit Pritam (Asian Pacific Journal of Cancer Biology, 2025)
Background and Purpose: Thyroid cancer is a significant global health concern, and autoimmune thyroiditis, including Hashimoto’s thyroiditis and chronic lymphocytic thyroiditis, has been suggested as a potential risk factor. This meta-analysis aimed to investigate the association between autoimmune thyroiditis and thyroid carcinoma in the Indian population. Methods: A systematic search yielded 53 studies, of which six were included. Statistical analysis assessed the correlation between autoimmune thyroiditis and thyroid carcinoma. Results: The analysis reveals a significant association between autoimmune thyroiditis and thyroid carcinoma in the Indian population, primarily driven by Hashimoto’s thyroiditis. Conclusion: This study underscores the relevance of autoimmune thyroiditis as a potential risk factor for thyroid carcinoma in India. Further research is needed to confirm these findings and elucidate the underlying mechanisms.